2020
DOI: 10.21203/rs.2.24526/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic diversity and genotype multiplicity of Plasmodium falciparum infection in patients with uncomplicated malaria in Chewaka district, Ethiopia

Abstract: Background Genetic diversity in Plasmodium falciparum poses a major threat to malaria control and elimination interventions. Characterization of the genetic diversity of P. falciparum strains can be used to assess intensity of parasite transmission and identify potential deficiencies in malaria control programmes, which provides vital information to evaluating malaria elimination efforts. This study investigated the P. falciparum genetic diversity and genotype multiplicity of infection in parasite isolates fro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…The K1-type for msp-1 and FC27-type for msp-2 were the most predominant alleles. These ndings are consistent with data previously reported in Madagascar [11] and in different settings such as Africa (Nigeria [15,22], Congo Brazzaville [25], Mauritania [26], Benin [27], Gabon [28,29], Ivory Coast [30], Cameroon, [31], Ethiopia [32][33][34][35]), India [36] or Southeast Asia [37]. However, they contrast with recent reports from Myanmar [38] that showed that MAD20 and 3D7 were the most prevalent alleles.…”
Section: Discussionsupporting
confidence: 88%
“…The K1-type for msp-1 and FC27-type for msp-2 were the most predominant alleles. These ndings are consistent with data previously reported in Madagascar [11] and in different settings such as Africa (Nigeria [15,22], Congo Brazzaville [25], Mauritania [26], Benin [27], Gabon [28,29], Ivory Coast [30], Cameroon, [31], Ethiopia [32][33][34][35]), India [36] or Southeast Asia [37]. However, they contrast with recent reports from Myanmar [38] that showed that MAD20 and 3D7 were the most prevalent alleles.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have investigated the genetic diversity of P. falciparum in endemic regions in Africa, South America and Asia [15][16][17], including a few studies from Ethiopia [18][19][20][21]. Most of these studies were conducted in moderate to high trasmision settings and showed high genetic diversity and MOI.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals living in areas of high malaria transmission intensity can concurrently be infected with multiple and genetically distinct clones of P. falciparum resulting in MOI (Kidima & Nkwengulila, 2015;Sondén et al, 2015). Genetically diverse and multiple P. falciparum infections occur in both asymptomatic (Abamecha et al, 2020) and symptomatic (Soulama et al, 2009) malaria patients. P. falciparum genetic diversity and MOI enhance parasite virulence, malaria pathology and evasion of the immune response (Jensen, Adams, & Hviid, 2020;Josling & Llinás, 2015;Sondo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%